The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/hbm.25845
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning derived automated ASPECTS on non‐contrast CT scans of acute ischemic stroke patients

Abstract: Ischemic stroke is the most common type of stroke, ranked as the second leading cause of death worldwide. The Alberta Stroke Program Early CT Score (ASPECTS) is considered as a systematic method of assessing ischemic change on non-contrast CT scans (NCCT) of acute ischemic stroke (AIS) patients, while still suffering from the requirement of experts' experience and also the inconsistent results between readers.In this study, we proposed an automated ASPECTS method to utilize the powerful learning ability of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…DL methods are also being explored, with encouraging results [ 41 ]. Several studies have demonstrated AI ASPECTS scoring performance to be equal to that of experienced neuroradiologists [ 42 , 43 , 44 , 45 , 46 , 47 ]. Albers et al showed that RAPID ASPECTS was more accurate than experienced readers in identifying early ischemia when compared to the corresponding DWI results [ 48 ].…”
Section: Ischemic Strokementioning
confidence: 99%
“…DL methods are also being explored, with encouraging results [ 41 ]. Several studies have demonstrated AI ASPECTS scoring performance to be equal to that of experienced neuroradiologists [ 42 , 43 , 44 , 45 , 46 , 47 ]. Albers et al showed that RAPID ASPECTS was more accurate than experienced readers in identifying early ischemia when compared to the corresponding DWI results [ 48 ].…”
Section: Ischemic Strokementioning
confidence: 99%
“…All images were processed using a research portal platform. 1 (1) NCCT images analysis: For patients with ischemic stroke, the Alberta stroke program early CT score (ASPECTS) could be used to evaluate the early changes in middle cerebral artery territory (MCAT) (Cao et al, 2022). Briefly, the brain was segmented into 20 ASPECTS regions.…”
Section: Imaging Characteristicsmentioning
confidence: 99%
“…Meanwhile, the mean CT intensity (unit: HU) was also collected for all regions. Note that the ASPECTS values were evaluated automatically based on our previous proposed deep learning algorithm (Cao et al, 2022). ( 2) CTP images analysis: The raw CTP images were calculated, and parameter maps were obtained.…”
Section: Imaging Characteristicsmentioning
confidence: 99%
“…3 To address this, artificial intelligence tools have been developed to assist with early stroke evaluation by automating determination of ASPECTS. [4][5][6] However, ASPECTS estimated using automated methods may be be sensitive to NCCT reconstruction method. 7 The purpose of this work was to perform initial investigations into the effects of CT reconstruction kernel and slice thickness on automated ASPECTS determination.…”
Section: Introductionmentioning
confidence: 99%